Effects of carbohydrate ingestion 15 min before exercise on endurance running capacity - Tokmakidis, S. P.; Karamanolis, I. A. (Applied Physiology, Nutrition, and Metabolism, 2008)
This study examined the effects of pre-exercise carbohydrate ingestion on exercise metabolism and endurance running capacity. Eleven active subjects (VO2 max 49.0 ± 1.7 mL/kg·min, mean ± SE) performed two exercise trials 15 min after ingesting glucose (G; 1 g/kg body mass) and placebo (CON). Each subject ran on a level treadmill for 5 min at 60%, 45 min at 70%, and then at 80% of VO2 max until exhaustion. Serum glucose and plasma insulin reached their peak concentrations (p < 0.01) 15 min after glucose ingestion and declined at the onset of exercise. Serum glycerol concentrations were lower (p < 0.01) in the G trial than in the CON trial after 30 min of exercise to exhaustion. In addition, after 45 min of exercise to exhaustion, the levels of free fatty acids were lower in G than in CON (p < 0.05). No differences were observed in carbohydrate oxidation rates during exercise between treatments (G, 2.53 ± 0.08 g/min; CON, 2.40 ± 0.09 g/min). Time to exhaustion was 12.8% longer in G (p < 0.01) than in CON. These results suggest that glucose ingestion 15 min before prolonged exercise provides an additional carbohydrate source to the exercising muscle, thus improving endurance running capacity.